Análise da freqüência de aberrações cromossômicas em trabalhadores de curtumes de Franca-SP ocupacionalmente expostos a produtos químicos - Monteiro Neto, Moacir de Azevedo Bentes (2007)
The mutation defined as any qualitative and quantitative alteration to the genetic material, may occur in spontaneous or induced forms. It raises a great interest due to being directly related to a diversity of degenerative disease development, specially cancer. It has been estimated that millions of workers are exposed to different chemical products in their work routine .The region of Franca is characterized by its concentration of shoes factories and tanneries where a great variety of chemical products have been used. The aim of this paper was analyzing the frequency of chromosome aberrations (CA) in lymphocyte from periferic blood of individuals occupationally exposed to different chemical agents used in tannery industries from the municipality of Franca, besides control individuals. Twenty individuals volunteerily joined this work (10 tannery workers and 10 control) all of them were male, age group from 25 to 46 years old. The participants answered a pattern questionnaire with the aim to collect important characterized data such as age, exposition time to chemical agents, smoking habit and coffee and; or alcohol ingestion. A total of 100 metaphases individual were analysed, and for the calculus for mitotic index (MI) and the frequency of metaphasic cells was observed in an amount of 1000 cells division-individual. The results didn’t present difference between the MI calculated for two different groups. For the frequency of CA the values observed were 69 and 35 considering the “gaps”, and 34 and 18 excluding the “gaps“ for the exposed and control groups respectively. This data was analysed over a non-parametric test of Mann-Whitney with no meaningful difference. Despite these statistics results, a bigger frequency of CA in a workers’ group was related showing the importance and necessity of protection for professionals occupationally exposed. Key words: tannery, chromosomic aberrations, human lymphocytes.